Ação de drogas agonistas e antagonistas dos sistemas colinérgico e dopaminégico: estudo comportamental e neuroquímico em corpo estriado de rato - Noronha, Emmanuelle Coelho (2005)
In the study, the interaction between the dopaminergic and cholinergic systems through the study of behavioral (open field and catalepsy) and neurochemical (density of dopaminergic receptor (D1 and D2-like) and muscarinic (M1+M2-like)) effect in striatum rat was evaluated. The following drugs were used: mazindol (indirect dopaminergic agonist), apomorphine (D1-like and D2-like dopaminergic agonist), pilocarpine (M1-like muscarnic aginist), carbachol (M-2like agonist muscarinc), pirenzepine (M1-like antagonist muscarinic), atropine (non-selective M1 and M2 antagonist muscarinic), clozapina(non-typical neuroleptic). The results showed that the pimozida and carbachol, alone or associated, caused increase in the cataleptic response and reduction in the motor activity. The mazindol also increased the motor activity. In small dosage, the carbachol and mazindol increased the density of D1-like receptors. Isolated, the pimozida and atropine increased the density of the D1-like receptors in striatum whereas the atropine caused a reduction of D2-like receptors and upregulation of muscarinic receptors. This work suggests a relationship, between muscarinc receptors M1 and M2 and dopaminergic receptors D1 and D2, and that this relationship can occur in a positive and negative manner, depending on the selectivity and the dose of the used drug.